Pipeline Engineering Design, Failure, and Management - Rushd, Sayeed; Anwar Ismail, Mohamed (IntechOpen, 2023)
All around the world, pipelines ensure the economic transmission of essential fluids to different industries and residential buildings. The discipline of pipeline engineering covers a wide range of topics, including design, construction, operation, instrumentation, maintenance, integrity, management, corrosion, and failure. Probably the most significant subjects are design, failure, and management, as these specialties have direct impacts on all other aspects of pipeline engineering. This book focuses on some recent evidence-based developments in these fields. The chapters include experiment-, simulation-, and analysis-based studies. The contributing authors come from diverse geographical locations with strong experience in their respective fields. The technological aspects examined here would definitely reinforce a pipeline engineer's decision-making process.